Purification and Characterization of a Human Neutrophil Neutral Protease: THE NEUTRAL PEPTIDE-GENERATING PROTEASE - Coblyn, Jonathan S. (1979)
A human neutrophil neutral protease which generates a low molecular weight peptide from a plasma protein substrate and cleaves the basic amino acid ester substrates α-N-p-tosyl-l-arginine methyl ester HCl, α-N-benzoyl-l-arginine-methyl ester HCl, and α-N-carbobenzoxy-l-lysine-p-nitrophenyl ester has been purified to homogeneity and distinguished from the known lysosomal neutrophil proteases. The starting activity was obtained from purified human neutrophils by homogenization, sedimentation by low-speed centrifugation, and high salt elution of the insoluble material. Purification was achieved by aprotinin-affinity chromatography, precipitation at low ionic strength, and gel filtration. The overall recovery, relative to the activity in the starting eluate of the neutrophil fraction, was ≅50% with a 200- to 400-fold increase in specific activity. After treatment with diisopropylfluorophosphate to eliminate autodegradation, sodium dodecyl sulfate-polyacrylamide gel electrophoresis of reduced and unreduced protein gave a single protein band of 29,000-30,000 mol wt. The isoelectric point determined in sucrose gradients ranged from pH 7.8 to 8.3 with a peak at pH 8.0. This neutrophil protease, like cathepsin G and elastase, is composed of a single polypeptide chain of ≅30,000 mol wt, but differs from cathepsin G and elastase in its less cationic isoelectric point and its failure to cleave synthetic substrates presenting an aromatic amino acid ester linkage and alanyl peptide bonds, respectively.